2020
DOI: 10.1097/mej.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Association between collapse and serum creatinine and electrolyte concentrations in marathon runners: a 9-year retrospective study

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law.The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team.We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…While we demonstrated a mean increase of 2.0°C in core body temperature during the EHST, elevations in KIM-1 have typically occurred following more prolonged exercise 52 and can help explain why we did not observe significant changes in KIM-1 despite moderate hyperthermia, which is suggested to cause elevations in AKI biomarkers 6 . The combination of physical exertion, thermal strain, and heat illness has been associated with rises in serum creatinine 53 , although it is unclear if these changes reflect kidney injury. As such, we included KIM-1 as a more specific AKI marker, and clearly the minimal response was not associated with any significant kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…While we demonstrated a mean increase of 2.0°C in core body temperature during the EHST, elevations in KIM-1 have typically occurred following more prolonged exercise 52 and can help explain why we did not observe significant changes in KIM-1 despite moderate hyperthermia, which is suggested to cause elevations in AKI biomarkers 6 . The combination of physical exertion, thermal strain, and heat illness has been associated with rises in serum creatinine 53 , although it is unclear if these changes reflect kidney injury. As such, we included KIM-1 as a more specific AKI marker, and clearly the minimal response was not associated with any significant kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…La investigación y literatura actual ha centrado el foco en el enfermo cardiaco grave en este tipo de situaciones 2 , sin embargo, no es despreciable la gran variedad de atenciones que se realizan en estos eventos implicando al resto de aparatos y sistemas del organismo. Deshidrataciones, presíncopes y alteraciones endocrino-metabólicas, entre otras, son muy frecuentes en estos pacientes y normalmente implican la presencia de alteraciones en los parámetros de la analítica sanguínea 3,4 .…”
Section: Introductionunclassified
“…McCubbin et al concluded from their recent study about modeling sodium requirements that targeted sodium replacements may be unnecessary in elite marathoners [17]. Moreover, Fitzpatrick et al discovered in a 9-year retrospective study an association between a collapse and serum creatinine and electrolyte concentrations in marathon runners [18]. Furthermore, evidence synthesis regarding the risk factors for EAH is warranted.…”
Section: Introductionmentioning
confidence: 99%